Endocarditis infecciosa sobre prótesis valvular aórtica - Moreno-Martínez, Francisco L.; Gómez Guindal, José A.; Portela, Francisco; González Gallego, Rocío S. (CorSalud, 2020)
Endocarditis infecciosa sobre prótesis valvular aórtica